Analisis Keadilan Upah Dalam Perspektif Hukum Ketenagakerjaan Dan Sustainable Development Goals (SDGs) - Cheryl Michaelia Ongkowiguno; Slamet Tri Wahyudi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes wage injustice among honorary teachers in Indonesia through the lens of labor law, Sustainable Development Goals (SDGs), and constitutional values. Despite their functional role in executing tasks equivalent to national defense (bela negara), honorary teachers remain trapped in severe legal ambiguity due to dual civil service systems between Labor Law and the Civil Service Apparatus (ASN) framework. Empirical data reveals 74% of honorary teachers earn below the City/Regency Minimum Wage (UMK), with 20.5% receiving less than IDR 500,000 monthly. Contractual uncertainty and wage dependency on limited School Operational Assistance Funds (maximum 50% allocation) create structural design defects resulting in systematic economic injustice. This violation contravenes Article 28D Paragraph (2) of the 1945 Indonesian Constitution guaranteeing fair and adequate remuneration, and contradicts Indonesia's SDG commitments, particularly SDG 1 (No Poverty), SDG 4 (Quality Education), SDG 8 (Decent Work), and SDG 10 (Reduced Inequality). Using normative legal methodology with statute approach and conceptual approach toward Welfare State principles and distributive justice, findings demonstrate state failure in implementing the Fifth Principle of Pancasila (Social Justice) and constitutional economic protections. Solutions require reconfigured dedicated funding mechanisms (non-BOS), clarification of long-term employment status, and fulfillment of constitutional state obligations through earmarked General Allocation Funds to achieve adequate minimum wages nationwide, thereby realizing constitutional rights and SDG targets.